Ekshibisi, Kekuasaan, dan Identitas: Tafsir atas Politik Representasi Tiga Museum di Yogyakarta - Khidir Marsanto (Antropologi Indonesia, 2012)
This article will clarify political representation of exhibition at Ullèn Sentalu Museum, Monumen Jogja Kembali, and Affandi Museum. These three museums are considered as proponent of Yogyakarta’s identity as the central of Javanese culture, struggle city, and the barometer of Indonesian fine art. The issue then, is it true that in the exhibitions’ at the three museums are appropriate with the identity of Yogyakarta, or in the contrary, the exhibitions have no correlation with this city’s identity discourse. There is a possibility that museum precisely bringing self-interest for specific purposes. Therefore, this paper needs to observe how the exhibitions at these museums were implemented. Through interpretive approach, the exhibition at the museum may be analogous similar with language phenomenon, and hence museum is considered as text that can be read and interpreted. Exhibition at the museum was developed within framework of thoughts (ideology), motives, and specific discourses, which all of these are articulated through a set of symbols (collection), that arranged with special layout procedure (display procedure). Thus, museum becomes ‘political’ since, in this perspective, museum has power over the formation of discourse through their exhibition. Keywords: museum critics, museum politics, political representation, hermeneutic anthropology, display interpretation.